Extraction and purification of C-phycocyanin from dry Spirulina powder and evaluating its antioxidant, anticoagulation and prevention of DNA damage activity - Suresh P. Kamble, Rajendra B. Gaikar, Rimal B. Padalia and Keshav D. Shinde (Journal of Applied Pharmaceutical Science, 2013)
C-Phycocyanin (C-PC) is a phycobiliprotein found in blue green algae, such as Spirulina platensis, is often used as a dietary nutritional supplement and exhibit a variety of pharmacological properties. In this regard, extraction, partial purification and antioxidant, anticoagulation and prevention of DNA damage activity of C-PC was investigated. In the present study, a simple and efficient method to extract C-PC from Spirulina platensis dry powder is reported. The extractions were carried out using two different methods: cold maceration and sonication method. The extraction using cold maceration method proved to be the most efficient method. Obtained crud C-PC was purified by ammonium sulphate precipitation, dialysis and gel filtration and presented a final extraction yield of 3.27±0.09 mg/ml with a purity ratio of 2.317±0.08. When it was evaluated as an antioxidant in vitro, it was able to scavenge nitric oxide. C-PC showed significant anticoagulation and prevention of DNA damage activity.
Keywords: Spirulina, Extraction, C-phycocyanin, DNA damage, SD